Host-plant defence against Striga spp.: reconsidering the role of tolerance - Rodenburg, J.; Bastiaans, L. (Wiley, 2011)
Parasitic weeds of the genus Striga cause high yield losses in cereal crops across Africa. Host-plant defence against Striga spp. can be an effective control strategy. It ideally consists of resistance, to reduce infection, complemented with tolerance, to mitigate the effects of infection. As resistance against Striga spp. can both minimise yield losses and reduce future infestation levels in infested fields, current breeding efforts are mainly directed towards this trait. Because it is nearly impossible to screen for tolerance on highly resistant genetic lines, tolerance is often neglected. Here, we argue reconsidering the role of tolerance, as recent findings regarding the physiological expression of tolerance offer a promising track for identifying the genetic background of tolerance. Identification of quantitative trait loci for tolerance would facilitate the inclusion of this trait in adapted cultivars with high levels of resistance, where its main role would be to function as a safety net in case the genetically highly variable parasite populations overcome host-plant resistance. Because Striga spp. are mainly prevalent in subsistence farming systems, we consider this an important addition and it is for this reason that we make a plea for a more prominent role of tolerance in present-day integrated management of this weed.